Phenotypicand Genotypic Characterization of Clinical Isolates of Intracellular Adherent–Invasive Escherichia coli Among Different Stages, Family History, and Treated Colorectal Cancer Patients in Iran - Kamali Dolatabadi, Razie; Fazeli, Hossein; Emami, Mohammad Hassan; Karbasizade, Vajihe; Maghool, Fatemeh; Fahim, Alireza; Rahimi, Hojatollah (Frontiers in Cellular and Infection Microbiology, 2022)
There is increasing evidence showing that microbial dysbiosis impacts the host's health and cancer risk. A relationship between adherent invasive Escherichia coli (AIEC) and colorectal cancer (CRC) has been revealed. Cyclomodulins (CMs) are receiving increasing attention for carcinogenic changes. The incidence and features of intracellular AIEC, cyclomodulin -encoding genes, and phylogenetic grouping and genetic relatedness evaluation in this study were investigated. E. coli strains were isolated from the colorectal biopsies. Adhesion and invasion assays and intramacrophage cells survival test were performed to separate the AIEC isolates. Virulence genotyping for htrA, dsbA, chuA, lpfA genes and cyclomodulin toxins were done. Phylogenetic grouping of isolates was determined. Subsequently, Rep-PCR fingerprinting was performed. A total of 24 AIEC phathovare were isolated from 150 patients. The prevalence of htr, dsbA, and lpfA factors were 70.83% and chuA was 91.66%. The frequencies of cyclomodulins toxins were as follows: cnf1 29.2%, cnf2 25%, colibactin 29.2%, cdt 4.2% but cif was not found. Among the AIEC isolates, 4.2%, 4.2%, 54.2%, 29.2%, and 8.3% with phylotypes A or C, B1, B2, D, and E were identified, respectively. Left-sided colon carcinoma and adenocarcinoma T≥1 stage (CRC2), colonized by B2 AIEC-producing CMs more often than the samples from the other groups. Close genetic relatedness was observed in AIEC isolates with Rep-PCR.